Active permanent magnet support for a superconducting magnetic-bearing flywheel rotor. - Sivrioglu, S. (IEEE Transactions on applied superconductivity)
This paper proposes a novel active permanent magnet support approach to improve the lateral stiffness of a superconducting magnetic-bearing flywheel rotor system. An actual flywheel rotor system levitated with high-temperature superconducting magnetic bearings is modeled and then analyzed with a moving permanent magnet support placed at the top of the rotor. The active support principle defined in this study is based on moving the permanent magnet support 180° out of the phase with the rotor displacement. A complete dynamical equation of the flywheel rotor is derived including gyroscopic effects. Analysis showed the active support of the flywheel rotor with additional permanent magnet movements decreased the amplitude of flywheel rotor vibration considerably